Analysis of Power Coupling Device with Dual Planetary Gear Set based on Dynamic Programming - Shaohua Wang; Sheng Zhang (Jixie chuandong)
Aiming at two different kinds of power coupling devices with dual planetary gear sets， the equivalent lever is established to analyze the power split characteristics and the transmission efficiency of the devices. At the same time， the common operation modes of hybrid systems with these power coupling devices are divided. On this basis, the power component model of the engine，motors and the battery are also established. By introducing dynamic programming algorithm, taking the battery SOC as state variable and engine torque and speed as control variable, the fuel consumption of the vehicle is set as the objective function for global optimization. Simulation results show that, under NEDC driving cycle, the compound-split power coupling device has superior fuel economy to the input-split power coupling device.